FRI0045 Evaluation of Articular Cartilage Change of Knee Joint in Rheumatoid Arthritis Using T1ρ Mapping Magnetic Resonance Imaging. (9th June 2015) - Osaki, K.; Okazaki, K.; Takayama, Y.; Mzu-uchi, H.; Hamai, S.; Kuwashima, U.; Murakami, K.; Kawanami, S.; Honda, H.; Iwamoto, Y.
Abstract : Background: The early diagnosis and treatment of rheumatoid arthritis (RA) have been recognized as an important strategy to halt progression of the disease. However, it is still not established whether anti-rheumatic reagents are able to protect cartilage from inflammatory damage. Furthermore, it is not known whether the depletion of cartilage matrix occurring in early stages of the disease is reversible. In recent years, T1rho mapping have attracted attention as relatively new magnetic resonance imaging (MRI) methods that can be used to evaluate the quality of cartilage matrix. T1rho values are known to correlate with cartilage proteoglycan content. This method is useful and non-invasive technique to detect early qualitative change of articular cartilage that is undetectable in radiograph. Assessing cartilage quality by in vivo imaging is useful to evaluate the beneficial effects of anti-rheumatic reagents for articular cartilage. Objectives: One of the purposes in this study is to evaluation early cartilage degeneration of RA patients using T1rho mapping. Another purpose is to assess changes of cartilage degeneration over time using T1rho mapping. Methods: In this study, 21 knees of RA patients with symptoms in knee and 10 knees of healthy volunteers were imaged with a 3.0 T magnetic resonance scanner. Ten of the RA patients could be taken follow MRI at 1 year after the pharmaceutical intervention using methotrexate or biologic agents from at the baseline MRI. The region of interest (ROI) was defined in the cartilage at the femoral groove area with least weight bearing load (Figure ). Patients were partitioned into five groups: healthy volunteers (group A, n=10), RA patients whose knee radiographs were Larsen grade 0 or I (group B, n=13), Larsen grade II-IV (group C, n=10), follow-up patients (n=10) at baseline (group D1) and at one year later (group D2). To assess disease activity, we calculated DAS28CRP at the time of MRI. To investigate early qualitative change of articular cartilage that is undetectable in radiograph, we compared T1rho values between group A, group B and group C. To investigate whether anti-rheumatic reagents are able to protect cartilage from inflammatory damage, we compared group D1 with D2. Results: DAS28CRP was 3.24±1.22 in group B, 3.98±1.46 in group C, 3.42±1.57 in group D1 and 1.87±0.85 in groupD2. Median T1ρ values were significantly higher in group B (50.2±4.0 ms) and group C (51.8±5.7 ms) compared with those in group A (46.1±3.3 ms) (group A vs B: P =0.0289, group A vs C P=0.0088). Median T1ρ values were significantly higher in group D1 (49.4±3.5 ms) compared with those in group D2 (46.2±3.0 ms) (P=0.0117). Conclusions: T1rho values of RA patients with undetectable degenerative change in radiograph were significantly increased than healthy control. Although it was a small number of cases, T1rho values at follow-up were significantly decreased compared with the values at baseline. References: Tsushima H, Okazaki K, Takayama Y et al (2012) Evaluation of cartilage degradation in arthritis using T1ρ magnetic resonance imaging mapping.Rheumatol Int 32:2867-2875 Disclosure of Interest: K. Osaki: None declared, K. Okazaki Grant/research support from: Pfizer, Inc, Y. Takayama: None declared, H. Mzu-uchi: None declared, S. Hamai: None declared, U. Kuwashima: None declared, K. Murakami: None declared, S. Kawanami: None declared, H. Honda: None declared, Y. Iwamoto: None declared